Critical insights in India: factors linked to ICU admission and mortality in influenza cases - Sahu, Monalisa; Malla, Sreeharshita; Kola, Venkat Raman (International Journal Of Community Medicine And Public Health, 2025)
Background: Influenza remains a major public health concern globally, causing significant morbidity and mortality. Severe influenza infections are often complicated by pulmonary co-infections and may require intensive care, but data on risk factors contributing to worse outcomes in Indian settings are limited. The objective of the study was to identify risk factors associated with severe influenza outcomes and to assess the prevalence of pulmonary co-infections among hospitalized influenza patients. Methods: A retrospective cross-sectional study design was opted. Three-years data from 625 laboratory-confirmed influenza patients was analysed. Regression models were used to identify predictors of ICU admission and mortality. Results: Most patients aged above 18 years and there was higher male population. Influenza A/H1N1 was the most common subtype (66.88%). 39.1% patients required ICU admission and 33.4% had mortality. Influenza A/H1N1 infection, age >18 years, female gender, obesity (BMI >30 kg/m²), respiratory failure, viral pneumonia, renal insufficiency, stroke, diabetes mellitus, and presence of dyspnea or fever were associated with increased odds of ICU admission. Independent risk factors for mortality included Influenza A/H1N1 infection, age >65 years, obesity, hypertension, hepatic disease, respiratory failure, bacterial co-infections, and prior use of immunosuppressants or antibiotics after admission. Pulmonary co-infections were identified in 29.92% (viral) and 24.96% (bacterial) of cases, with Klebsiella pneumoniae and RSV being the predominant pathogens. Conclusions: Severe influenza outcomes were significantly associated with specific host factors, viral subtypes, and secondary infections. Targeted prevention strategies, early intervention, and improved vaccination coverage, especially among high-risk groups, may reduce the burden of severe influenza-related illness and mortality in India.